Response to various water regimes of the physiological aspects, nutritional water productivity, and phytochemical composition of bush tea (Athrixia phylicoides DC.) grown under a protected environment - Rumani, Muneiwa; Mabhaudhi, Tafadzwanashe; Ramphinwa, Maanea Lonia; Ramabulana, Anza-Tshilidzi; Madala, Ntakadzeni Edwin; Magwaza, Lembe Samukelo; Mudau, Fhatuwani Nixwell (MDPI, 2024)
The influence of water regimes on plants is crucial for integrating bush tea (Athrixia phylicoides DC.) into strategies in Sub-Saharan Africa to tackle food and nutritional insecurity by considering physiological aspects, nutritional yield, nutritional water productivity, and metabolite composition. The objective of the study was to determine the physiological aspects, including leaf gas exchange and chlorophyll fluorescence, nutritional yield, nutritional water productivity, and metabolite composition of bush tea under varying water regimes. The tunnel experiment was laid out in a randomized complete block design (RCBD) with treatments consisting of three water regimes: 100% of crop water requirement (ETa), 30% of ETa, and a control (no irrigation), all replicated three times. The morphological aspects were recorded on a weekly basis. However, yield, nutrient content, nutritional water productivity (NWP), and phytochemical composition were determined at harvest. The phytochemical analysis by liquid chromatography mass spectrometry (LC-MS), coupled with visualization of the detected chemical spaces through molecular networking, indicated Athrixia phylicoides DC. to be rich in various bioactive compound derivatives, including methyl chlorogenate, flavonoids, tartaric acid, caffeoylquinic acid, and glutinane. The results showed that 30% ETa enhanced plant growth, nutrient content, and nutritional water productivity compared to other water treatments. Nevertheless, 100% ETa yielded more (95.62 kg ha−1) than 30% ETa (60.61 kg ha−1) and control (12.12 kg ha−1). The accumulation of chlorogenic acids was higher under 30% ETa compared to 100% ETa and control. Therefore, this study is the first to determine the accumulation of various bioactive compounds in bush tea leaf extracts under varying water regimes. This confirms that in areas with low water availability, bush tea is well adapted for production without limiting nutrients.
Keywords: herbal tea; water treatments; water stress; nutrient content; water-use efficiency; growth development; yield; molecular network